THE REALIZATION OF THE RIGHT FOR INFORMATION IN JOURNALISTIC PRACTICES - Koterlin, I. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The essence as well as the legislative understanding of the notion "right for information" is observed in the context of possible freedom and right abuse in journalistic practices. The attention is paid to establishing the legislative borders of the admissible behavior of a journalist when embodying their right for information. The lawmaking prohibitions concerning the spread of socially harmful information is being highlighted, and, vice versa - the lawmaking provision through the journalistic practice the right of publicity for the socially-important information.